2018
DOI: 10.1002/aoc.4513
|View full text |Cite
|
Sign up to set email alerts
|

Visible‐light‐driven photocatalytic degradation of fenpyroximate in rotating packed bed reactor using Fe3O4@PbS@Ni2P magnetic nanocomposite photocatalyst: Response surface modelling and optimization

Abstract: A highly efficient rotating packed bed photocatalytic reactor based on Fe3O4@PbS@Ni2P composite for the degradation of fenpyroximate (FP) as an acaricide in agriculture is described. The visible‐light‐driven photocatalyst was characterized using various techniques. The interaction of operational parameters consisting of rotational speed (400–1200 rpm), photocatalyst dosage (0.20–0.40 g l−1), solution flow rate (0.10–0.50 l min−1), aeration rate (15–35 l min−1), FP initial concentration (5–45 mg l−1), pH (2–10)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…43 The statistical significance of the obtained model was appraised through the analysis of variance (ANOVA) via a comprehensive collection of mathematical and statistical tests including F-value, Pvalue, lack of fit, the regression correlation squared (R 2 ), adjusted Rsquared (R adj 2 ), predicted R-squared (R pred 2 ), and the predicted residual error sum of squares (PRESS). 44,45 Eventually, the justified model was employed for providing 3D response surface plots and evaluation of the interactions among the operational parameters. cm −1 , C−O vibration at 1380 cm −1 , and CO peak at 1710 cm −1 .…”
Section: Methodsmentioning
confidence: 99%
“…43 The statistical significance of the obtained model was appraised through the analysis of variance (ANOVA) via a comprehensive collection of mathematical and statistical tests including F-value, Pvalue, lack of fit, the regression correlation squared (R 2 ), adjusted Rsquared (R adj 2 ), predicted R-squared (R pred 2 ), and the predicted residual error sum of squares (PRESS). 44,45 Eventually, the justified model was employed for providing 3D response surface plots and evaluation of the interactions among the operational parameters. cm −1 , C−O vibration at 1380 cm −1 , and CO peak at 1710 cm −1 .…”
Section: Methodsmentioning
confidence: 99%
“…[62] In the ANOVA analysis, when the data related to the p-value was determined to be lower than 0.05, the fitted model would be proper for predicting the photocatalytic degradation process at a confidence level of 95 %. [63,64] Furthermore, the lack-of fit (LOF) of the model should be insignificant to well represent the high performance of the model for providing reasonable data. [63,64] Accordingly, the designated data to the p-value and LOF amount in Table 3, clearly revealed that the designed in which, parameters with a positive sign (+) and a negative sign (À ) have a positive and negative influence on the CEF photocatalytic degradation process, respectively.…”
Section: Methods Modelingmentioning
confidence: 99%
“…The high value of R 2 (0.9996) and the adjusted R 2 (0.9992), and their closeness to 1.0 shows a very reasonable agreement between the observed results and the predicted ones. [64] To obtain further insight into the accuracy of the model in the CEF degradation process, the predicted values obtained from the respective model versus the measured experimental data (actual values) are depicted in Figure 11a. As it is apparent, the predicted data are entirely close to the experimental ones, which successfully confirmed that the actual values are well agreed with the predicted results, in accordance with the proposed polynomial equation.…”
Section: Methods Modelingmentioning
confidence: 99%